Redox‐Active Crystalline Coordination Catalyst for Hybrid Electrocatalytic Methanol Oxidation and CO2 Reduction - Sun, Sheng‐Nan; Dong, Long‐Zhang; Li, Jia‐Ru; Shi, Jing‐Wen; Liu, Jiang; Wang, Yi‐Rong; Huang, Qing; Lan, Ya‐Qian (Angewandte Chemie International Edition, 2022)
Hybrid CO2 electroreduction (HCER) is recognized as an important strategy to improve the total value of redox products and energy conversion efficiency. In this work, a coordination catalyst model system (Ni8‐TET with active oxidation sites, Ni‐TPP with active reduction sites and PCN‐601 with redox‐active sites) for HCER was established for the first time. Especially, PCN‐601 can complete both anodic methanol oxidation and cathodic CO2 reduction with FEHCOOH and FECO over 90 %. The performance can be further improved with light irradiation (FE nearly 100 %). DFT calculations reveal that the transfer of electrons from NiII8 clusters to metalloporphyrins under electric fields results in the raised oxidizability of Ni8 clusters and the raised reducibility of metalloporphyrin, which then improves the electrocatalytic performance. This work serves as a well‐defined model system and puts forward a new design idea for establishing efficient catalysts for hybrid CO2 electroreduction. The transfer of electrons from electron‐rich metal clusters (oxidation active sites) to electron‐deficient metalloporphyrins (reduction active sites) leads to stronger oxidizability of Ni8 clusters and stronger reducibility of metalloporphyrin. The enhanced oxidizability of Ni8 and reducibility of metalloporphyrin, therefore, result in improved methanol electrooxidation and CO2 electroreduction with the bifunctional crystalline coordination catalyst.